Analisis Pengaruh Pendapatan Pajak Reklame, Pajak Bumi Dan Bangunan, Pajak Hiburan, Pajak Air Tanah, Terhadap Pendapatan Asli Daerah Kota Tobelo Kab Halmahera Utara Tahun Anggaran 2017 – 2020 - Lis Lestari Sukartiningsih; Dahman Faisal (Universitas Katolik Widya Karya Malang, 2024)
This research aims to analyze the influence of advertising tax revenue, land and building tax, entertainment tax and groundwater tax on the local income of Tobelo City, North Halmahera Regency. This type of research is explanatory research with primary and secondary data sources. Field study and literature study data collection methods using observation, interview and documentation data collection techniques. The research population is the realization of the regional income budget of Tobelo City, North Halmahera Regency, census sampling method. Data analysis techniques use quantitative descriptive statistical analysis, classical assumption tests, and hypothesis testing. The results of simultaneous multiple linear regression analysis of advertising tax, land and building tax, entertainment tax and groundwater tax have a significant effect on local original income. Partially, advertising tax, land and building tax, entertainment tax and groundwater tax do not have a significant effect to local original income.